A análise de Jean-Jacques Rousseau sobre o Projeto de Paz perpétua do abade de Saint-Pierre - Costa, Alexsander (2015)
The numerous political theories of the modern time were committed to thesocial-political and economic restructuring of the European States, but parallel to those conceptions emerged proposals of a broader range regarding the concern with the harmony among the States and their respective external safety, that is, they envisioned an International System among the European States. In that purpose, the Project of peace by the abbé de Saint-Pierre which glimpses perpetual peace in Europe under institutionalized conditions in order to legitimate a space that aims at facilitating a unified market among the member States. In this context, the sovereign role stands out, given the fact that he is the mediator between the interests of the State and the objectives proposed by the International System of States. However, according to Jean-Jacques Rousseau’s point of view it is evident that the thought of Saint-Pierre is impregnated by a naivety regarding the sovereigns’ government policy and, moreover, for believing that, mediated by a confederal assembly, the princes would voluntarily agree to be part of this project of perpetual peace. Nevertheless, Rousseau does not consider impossible the realization of this project, however, to achieve peace it is necessary force. Therefore, the comprehension of this debate was only possible guided, mainly, by the analyses of the primary works of such thinkers and the theoretical basis of the experts that is necessary, for instance, Evaldo Becker, Gelson Fonseca Jr., Luiz Felipe de Andrade e Silva Sahd, José Oscar de Almeida Marques, José Benedito de Almeida Jr. who enabled a broad comprehension of the purpose to which we dedicated ourselves in this research, allowing the understanding of thekey concepts elaborated by the Genevan philosopher and the themes that concern the relationship between States.